1992
DOI: 10.1111/j.1365-2559.1992.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma in Kanazawa, Japan: prognostic significance of histological subtypes

Abstract: A retrospective analysis of 183 papillary thyroid carcinomas was made in order to assess the prognostic factors related to survival. The following factors were found to adversely affect the prognosis: trabecular subtype of papillary carcinoma, the extent of the primary tumour, regional lymph node involvement, the presence of distant metastases, old age, male sex and the extent of the neck dissection. The presence of the follicular variant of papillary carcinoma and the extent of the thyroidectomy did not influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 30 publications
1
50
1
Order By: Relevance
“…The published data on the prognostic significance of lymph node metastasis in PTC remains controversial. Some studies have shown that the presence of cervical lymph node metastases or mediastinal and bilateral cervical lymph node metastases was associated with greater mortality (Sellers et al 1992, Mazzaferri & Jhiang 1994, Lin et al 1999) and increased recurrence rates (Mazzaferri et al 1977, McConahey et al 1986, Simpson et al 1987, DeGroot et al 1990, Akslen & Myking 1992, Mizukami et al 1992, Lin et al 1999. However, other studies showed that the presence of lymph node metastases did not significantly impact on cancer mortality (Tubiana et al 1985, McConahey et al 1986, Simpson et al 1987, DeGroot et al 1990, and even had a lower mortality rate than those without nodal metastases (Cady et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The published data on the prognostic significance of lymph node metastasis in PTC remains controversial. Some studies have shown that the presence of cervical lymph node metastases or mediastinal and bilateral cervical lymph node metastases was associated with greater mortality (Sellers et al 1992, Mazzaferri & Jhiang 1994, Lin et al 1999) and increased recurrence rates (Mazzaferri et al 1977, McConahey et al 1986, Simpson et al 1987, DeGroot et al 1990, Akslen & Myking 1992, Mizukami et al 1992, Lin et al 1999. However, other studies showed that the presence of lymph node metastases did not significantly impact on cancer mortality (Tubiana et al 1985, McConahey et al 1986, Simpson et al 1987, DeGroot et al 1990, and even had a lower mortality rate than those without nodal metastases (Cady et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Poor prognostic factors include age (N50 years), male sex, increased tumor size, lack of encapsulation, extrathyroidal extension, multicentricity, and distant metastases at presentation [1,11,23,36,37]. For some authors, a lymphocytic stroma reaction is associated with an improved prognosis [6,32].…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases were a risk factor for recurrence, and they were most numerous in the papillary type of carcinoma (Table 2), as described earlier (Mazzaferri & Jhiang 1994, Sclumberger 1998. In some, but not all, studies (Hay 1990, Mazzaferri & Jhiang 1994, local lymph node involvement has been associated with an increased risk of tumour recurrence and also with DTC-related mortality (Mazzaferri & Jhiang 1981, Mizukami et al 1992, Schlumberger & Pacini 1999. The prognostic impact of regional lymph node metastases still remains a controversial issue.…”
Section: Discussionmentioning
confidence: 99%